Decision making using game theory : an introduction for managers - Kelly, Anthony, 1957- (Cambridge University Press, 2003)
This book explains how game theory can predict the outcome of complex decision making processes, and how it can help you to improve your own negotiation and decision making skills. Clear examples and helpful diagrams are used throughout, and the mathematics is kept to a minimum.